NEPHROTIC SYNDROME IN 2 YEARS OLD CHILD - Rahma Putri Kinasih (Fakultas Kedokteran Universitas Lampung, 2014)
Nephrotic syndrome is a chronic glomerular disease most often in children. The incidence of nephrotic syndrome at 2-7 per 100.000 children per year and a prevalence at 12-16 per 100.000 children. In Indonesia, nephrotic syndrome was reported at 6 per 100.000 children per year. Ratio of boys and girls is 2:1. Until the mid-20th century, the morbidity of nephrotic syndrome in children is still high, exceeding 50%. A boy, 2 years old, accompanied with chief complaint of body swollen or puffy, swollen at the location of the eyelid region (puffy face), chest, abdomen, arms and legs, presence of mild and moderate hypertension, presence of oliguria.Laboratory tests results obtained serum albumin level of 1.4 g/dl (hypoalbuminemia), blood cholesterol level 339 mg/dL (hypercholesterolemia), there is protein in the urine (proteinuria) 3+ or total protein 3.2 g/dl, the presence of erythrocytes in urine 15-20/hpf (microscopic hematuria). Management of non medical with sodium and calorie diet and medical management with diuretics such as furosemide at a dose of 2x15 mg to reduce edema. There is a mild degree hypertension were given captopril 2x6.25 mg. Given antibiotic drip Ceftriaxon 1.5 g. Corticosteroids are not given because the patient had hypertension. [J Agromed Unila 2014; 1(3):216-221]Keywords: edema, hypercholesterolemia, hypoalbuminemia, nephrotic syndrome, proteinuria